Evaluation of 3D-CRT Radiotherapy Treatment Planning with Radiobiological Effects in Patient-Specific 3D Printed Anthropomorphic Phantom Postmastectomy Breast Cancer Axillary Metastases - Endarko Endarko; Aditya Hariyanto; Siti Aisyah; Nandia Kavilani; Ahmad Syafi'i (Iranian Journal of Medical Physics)
Introduction: The aim of this study was to evaluate and measure the effectiveness of a particular radiotherapy treatment planning system, namely 3D conformal radiation therapy (3D-CRT), and radiobiological effects in postmastectomy breast cancer axillary lymph metastases using a patient-specific 3D printed anthropomorphic phantom of the right breast after surgery. Material and Methods: The chest wall and axilla were the two treatment targets for 3D-CRT planning techniques. Each target was subjected to variations of two and three irradiation fields, with a dose of 50.00 Gy and fractionation of 2.00 Gy. From the variations, the radiation dose received by planning target volume (PTV) chest wall, PTV-Axillary, and organs at risk (OARs) was evaluated to determine the best planning technique through dosimetry verification. The thermoluminescent dosimeter (TLD) 100 Chip and EBT3 film were employed to measure the radiation dose at the PTV and OARs. Results: The planning system evaluation based on dose volume histogram showed no significant difference (p = 0.993) between two and three irradiation fields in both the chest wall and axillary planning 3D-CRT technique. Normal tissue complication probability for OARs has values below 5%, while the smallest value was obtained for the left lung. Finally, the point dose verification between planning and measurement using TLD100 and EBT3 film indicated an average difference of 9.14% and 4.34%, respectively, with no significant difference. Conclusion: This study successfully demonstrated the dosimetry evaluation and radiobiological effects of postmastectomy right breast cancer treatment using a patient-specific 3D printed anthropomorphic phantom, which met the established standards.